NEURONAL TUMOR CELLS WITH EXCITABLE MEMBRANES GROWN in vitro - Nelson, Phillip (1969)
Mouse neuroblastoma cells grown in vitro are capable of generating action potentials in response to electrical stimulation. A wide spectrum of responses was observed with different cells ranging from passive responses to action potentials. A hypothesis is proposed concerning the acquisition of electrical excitability as neuroblasts mature into neurons.